rDNA-based characterization of a new binucleate Rhizoctonia spp. causing root rot on kale in Brazil - Kuramae, Eiko E. (2007)
In this paper we present the first report of the occurrence of a binucleate Rhizoctonia spp. causing hypocotyl and root rot in kale in Brazil. Rhizoctonia spp. were isolated from kale (Brassica oleracea var. acephala) with symptoms of hypocotyl and root rot. The isolates, characterized as binucleate Rhizoctonia spp., did not show an anastomosis reaction with any of the binucleate Rhizoctonia spp. testers used. The pathogenicity of the isolates was tested under greenhouse conditions; all isolates were pathogenic and showed different symptom severities on kale. The ITS-5.8S rDNA sequences of kale isolates and 50 testers (25 binucleate Rhizoctonia spp. and 25 Rhizoctonia solani) were compared in order to characterize the genetic identity of Rhizoctonia spp. infecting kale. The kale isolates showed genetic identities ranging from 99.3 to 99.8% and were phylogenetically closely related to CAG 7 (AF354084), with identities of 98.5 and 98.7%. It is suggested that the binucleate Rhizoctonia spp. causing hypocotyl and root rot on kale Brazil comprises a new AG not yet described.